1999
DOI: 10.1136/gut.45.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired human immune responses againstHelicobacter pylori and implications for vaccine development

Abstract: Naturally acquired human immune responses against Helicobacter pylori and implications for vaccine development PrefaceHelicobacter pylori has been identified as a causative agent of gastroduodenal pathology. Vaccination studies with mouse models have shown that immunisation with bacterial antigens can provide protection against infection, indicating that it may be possible to design vaccines which terminate colonisation by H pylori or prevent it from taking place. Here, we review critically current knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 126 publications
0
45
0
Order By: Relevance
“…127 More recently, several laboratories have shown that biopsies from gastric mucosa of normal, infected, and uninfected patients, revealed no or very low levels of mRNA of the classic Th2 cytokine IL-4. 137,138 These studies support the notion that most infected humans have a Th1 response, which does not eradicate H. pylori infection. It is therefore predictable that a Th2 response would be more effective.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 66%
See 1 more Smart Citation
“…127 More recently, several laboratories have shown that biopsies from gastric mucosa of normal, infected, and uninfected patients, revealed no or very low levels of mRNA of the classic Th2 cytokine IL-4. 137,138 These studies support the notion that most infected humans have a Th1 response, which does not eradicate H. pylori infection. It is therefore predictable that a Th2 response would be more effective.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 66%
“…In contrast, Th2 cells produce cytokines, which are responsible for eosinophil activation, inhibition of several macrophage functions that provide phagocyte-independent protective responses, and strong antibody production, particularly IgA and IgG, which are especially active on mucosal surfaces. 137,138 In the stomach, IL-12 and IL-10 production has been implicated in the selection of Th1 and Th2 cells, respectively. The relative predominance of IL-12 in the human stomach, regardless of whether it is infected or not, favors the development of a subset of helper T cells that tend to produce interferon gamma, which is associated with Th1 cells and enhanced cell-mediated immunity.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 99%
“…The immune response against H. pylori infection in mice and humans is ineffective in controlling the bacteria and appears to be biased towards a Th1 response (1,11,26,38,39,44). In contrast, the results of several studies in mice suggest that type 2 responses characterized by IL-4 secretion are important in immunity against this pathogen (18,26,27,36,38), but their significance has never been tested under stringent conditions.…”
Section: Several Groups Recently Identified Cd4mentioning
confidence: 76%
“…The initial migration of inflammatory cells into the gastric mucosa and their activation are believed to depend on the production of proinflammatory cytokines (2,8,17,(30)(31)(32). The inflammatory products from the polymorphonuclear cells (PMNs) and mononuclear cells (MNCs) are also thought to damage the epithelial layer and play a role in disease pathogenesis.…”
mentioning
confidence: 99%